Looking, seeing and believing in autism: Eye movements reveal how subtle cognitive processing differences impact in the social domain. Issue 8 (28th November 2015) - Benson, Valerie; Castelhano, Monica S.; Howard, Philippa L.; Latif, Nida; Rayner, Keith
Abstract : Adults with High Functioning Autism Spectrum Disorders (ASD) viewed scenes with people in them, while having their eye movements recorded. The task was to indicate, using a button press, whether the pictures were normal, or in some way weird or odd. Oddities in the pictures were categorized as violations of either perceptual or social norms. Compared to a Typically Developed (TD) control group, the ASD participants were equally able to categorize the scenes as odd or normal, but they took longer to respond. The eye movement patterns showed that the ASD group made more fixations and revisits to the target areas in the odd scenes compared with the TD group. Additionally, when the ASD group first fixated the target areas in the scenes, they failed to initially detect the social oddities. These two findings have clear implications for processing difficulties in ASD for the social domain, where it is important to detect social cues on‐line, and where there is little opportunity to go back and recheck possible cues in fast dynamic interactions. Autism Res 2016, 9: 879–887 . © 2015 International Society for Autism Research, Wiley Periodicals, Inc.